A 3-D micromechanical framework to study damage propagation and failure of printed aligned discontinuous fiber-reinforced composites. (March 2023) - Sepasdar, Reza; Niazi, Sina; Case, Scott W; Shakiba, Maryam
This paper presents a novel and efficient micromechanical framework for finite element simulation of damage and failure in 3-D printed aligned discontinuous fiber-reinforced composites. The framework can predict the initiation and propagation of different types of damage in the composite under tensile loading along the fibers' axis. The micromechanical framework includes the microstructural representation of the composite with explicit fibers and matrix in addition to linear expansions at the ends. Accurate constitutive equations are utilized for fibers, matrix, and fiber/matrix interfaces in the microstructural representation. Fibers' locations and lengths are generated randomly; based on a target distribution for the fibers' aspect ratios measured experimentally; within the microstructural representation. Optimal microstructural representative dimensions for reliable investigation of the mechanical response are computed by conducting sensitivity analyses. The accuracy of the micromechanical framework is validated versus the experimental results of a 3-D printed aligned discontinuous fiber-reinforced composite as the composite of interest. It is shown that the proposed framework can simulate various aspects of the mechanical response, including the failure pattern and stress-strain behavior. Subsequently, the sensitivity of the mechanical response of the composite to a few constitutive equation-related parameters, including the strength and fracture toughness of the fiber/matrix interfaces and the matrix strength, is investigated. The correlation between the studied parameters and the composite's strength and failure pattern is also analyzed and discussed. This paper delivers valuable guidance on the mechanical response of printed aligned discontinuous fiber-reinforced composites, eventually resulting in the paradigm-shifting design, manufacturing, and analysis of such advanced composites.